2013
DOI: 10.1097/ico.0b013e318269938d
|View full text |Cite
|
Sign up to set email alerts
|

Central Corneal Thickness Measurements With Different Imaging Devices and Ultrasound Pachymetry

Abstract: CCT measurements between OLCR-UP and OLCR-Pentacam are comparable and can be used interchangeably in clinical practice. However, SM underestimates CCT compared with the other methods, whereas Pentacam was found to be the least repeatable and took the longest time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 23 publications
5
43
1
7
Order By: Relevance
“…In spite of the amount of studies showing good correlation between UP and PC measurements, Tai et al [21] have claimed recently that the mean CCT by PC was 10 μm higher than that obtained using UP [10], which correlates well with our findings, showing significantly higher values in PC measurements.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In spite of the amount of studies showing good correlation between UP and PC measurements, Tai et al [21] have claimed recently that the mean CCT by PC was 10 μm higher than that obtained using UP [10], which correlates well with our findings, showing significantly higher values in PC measurements.…”
Section: Discussionsupporting
confidence: 82%
“…This was also reported by previously publications. Tai et al [21], in a study of 184 eyes, also found close agreement between LE and UP. This statement agrees with another study by Beutelspacher et al [22], who compared CCT measures obtained with OCT, LE, PC and UP showing good agreement.…”
Section: Discussionmentioning
confidence: 76%
“…Tai et al had reported that the mean CCT measurements by Pentacam HR were 10 μm more than that obtained using US pachymetry. 19 Other different studies also found that in Pentacam HR, CCT measurement to be thicker than ultrasound by 2.7 μm, and 6.4 μm, 8.0 μm, and 8.2 μm respectively 15,17,20,21 and in our study it was almost 5.346 um. Similarly, Hani et al concluded that Pentacam tends to overestimate CCT compared to US pachymetry in post Lasik patients.…”
supporting
confidence: 57%
“…Influence Factors: During the measurement, tear and eyelid will form a shelter to some extent (Tai et al, 2013); Due to its principle of optimal measurement, it is easy to be influenced by the transparency of cornea. Therefore, there are some requirements in symptoms of eye diseases for those under examination (Mencucci et al, 2012), such as caligo corneae and macular nebula.…”
Section: Pentacam Anterior Segment Analysis and Measurement Systemmentioning
confidence: 99%